OUTCOMES OF PREGNANCY AND CHILDBIRTH IN YOUNG WOMEN - Светлана Ивановна Елгина; Любовь Андреевна Кондратова (The Publishing House Medicine and Enlightenment, 2020)
Objective - to study the course of pregnancy, birth outcomes for the mother and fetus in young children. Materials and methods. A retrospective analysis of the medical histories of 400 women in the Kemerovo Regional Clinical Hospital, «Regional Perinatal Center», Kemerovo, for the period from 2015 to 2018. The Main group included 200 girls under 18 years of age, the control group included 200 girls aged 20-25 years. The obtained data were processed using the Statistica 6.0 program. For anthropometric data and Apgar assessment, the arithmetic mean values of quantitative indicators were calculated. In all statistical analysis procedures, the critical level of difference significance was assumed to be p equal to or greater than 0.05. Results. Young pregnant women showed an earlier age of first menstruation (p = 0.034), an earlier start of sexual life (p = 0.042), and the absence of contraceptive methods (p = 0.034) in comparison with women in the older age group. Smoking among young pregnant women was 10 times more than among women 20-25 years old (p = 0.024). Women in group 2 were officially married in 86.0 % of cases, while teenagers were only married in 13.0 % of cases (p = 0.026). The absolute majority in group 1 were pre-pregnant (96.0 %), while in group 2 only 64.0 % were pre-pregnant (p = 0.037). The term of the first appearance for pregnancy in young people was 23 weeks, in the 2nd group this indicator was on average 7 weeks (p = 0,017). In girls from group 1, extragenital pathology was significantly less common - in 9.0 % of cases (p = 0.025). There were no significant differences in pregnancy complications (gestational arterial hypertension (p = 0.123), preeclampsia (p = 0.233) in women of the two groups, as well as in the development of placental insufficiency (p = 0.204). The majority of patients in both groups gave birth at full term. However, preterm birth was significantly more common in the young group (15.0 % and 8.0 %, respectively, (p = 0.046). Cesarean section was also performed more often in young people (p = 0.033). There were no significant differences between weight (p = 0.264), height (p = 0.237), and Apgar score (p = 0.283) among newborns born to mothers of different ages. Conclusion. Thus, pregnant adolescents have a younger age of menarche, an earlier start of sexual life, more often nicotine dependence, lack of contraceptive methods, most of them are not married in comparison with the age group of women 20-25 years. The course of pregnancy in young women did not differ from older women. However, the birth was more often premature and operative. Birth outcomes for newborns did not differ.